An Analysis of the Internal Barriers Hindering Croatian Export Companies (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
Export represents the ultimate strategic necessity that ensures a positive impact on long-term sustainable development and the acquisition of international experience. Export strategy is created by the top management and largely depends on business policy. Each enterprise defines its own competitive strategy based on acquired resources. According to statistical data, Croatian companies are at a low level of internationalization and are not competitive on the global market. Therefore, this paper summarizes initial export barriers (so-called internal barriers), which arise within Croatian companies. These obstacles incorporate informational, functional and marketing features. Survey questionnaire revealed that major problems are reliability and the absence of exchange of information, as well as insufficient quality and availability of managerial personnel, especially those recruited for export activities. Consequently, companies have neither a representative nor mediator for the targeted foreign market. On the other hand, innovating and developing new products for export, especially providing after-sales services, have considerably risen.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.